2021
DOI: 10.1055/s-0041-1739367
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cochlear Implantation: Cognitive Function, Quality of Life, and Frailty in Older Adults

Abstract: This review examines the relationship between cochlear implantation and cognition and quality of life in older adults, as well as how frailty affects outcomes for older patients with cochlear implants. A growing body of evidence suggests that there is a strong association between hearing loss and cognitive impairment. Preliminary studies suggest that cochlear implantation in older adults may be protective against cognitive decline. While studies have observed a positive impact of cochlear implantation on quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 89 publications
(121 reference statements)
1
11
0
Order By: Relevance
“…The subjective hearing was measured with the short version of OI (34) that has 12 questions and three scales: (1) listening in a quiet setting (questions 1, 3, 5, 7), (2) listening with background noise (4,6,8,11,12), (3) directional listening (2, 9, 10). Responses to each of the 12 questions were rated 1 to 5 points.…”
Section: Oldenburg Inventory (Oi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The subjective hearing was measured with the short version of OI (34) that has 12 questions and three scales: (1) listening in a quiet setting (questions 1, 3, 5, 7), (2) listening with background noise (4,6,8,11,12), (3) directional listening (2, 9, 10). Responses to each of the 12 questions were rated 1 to 5 points.…”
Section: Oldenburg Inventory (Oi)mentioning
confidence: 99%
“…Cochlear implantation improves general hearing abilities, speech perception, and sound localization in patients with asymmetric hearing loss (AHL) ( 2 ), single-sided (unilateral) deafness (SSD) ( 3 ), and double-sided (bilateral) deafness (DSD) ( 4 ). Accumulating evidence suggests that the beneficial effects of implantation extend beyond the main indication (improvement of auditory abilities) and can positively impact cognition ( 5 7 ), health-related quality of life ( 6 , 8 ), and comorbid symptoms such as depression or anxiety ( 9 ). Additionally, the predominantly positive influence of implantation on tinnitus presence and tinnitus-induced distress is well-documented ( 9 , 10 ), although the exact mechanism of this phenomenon is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with moderate to profound bilateral sensorineural hearing loss, who demonstrate inadequate benefit from hearing amplification, may benefit from cochlear implantation, which has now become the standard of care and has been shown to improve global cognitive function, quality of life scores, and other long-term benefits (1)(2)(3). Recently, efforts have focused on performing implantation as atraumatically as possible, for residual hearing preservation and minimalization of triggers of fibrosis (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 shows how much their remaining hearing difficulties disturbed their activity capacity during the last two weeks. Four patients out of the forty-three included in the study canceled appointments at the clinic due to health-related issues that made it difficult to travel to the clinic (3) and the severe sickness of the patient's spouse (1). None of those four are among the patients with a change in the MSword score of more than 20 percentage points, as shown in Table 1.…”
Section: Figurementioning
confidence: 99%
“…The population in the world grows older, and age-related hearing loss is known to substantially impact quality of life [1,2]. Studies have found that the incidence of dementia is higher in people with self-reported hearing problems compared to hearing aid users or cochlear implant users [3].…”
Section: Introductionmentioning
confidence: 99%